Pengembangan Media KOJERUPAN Berbasis Smartbox untuk Meningkatkan Hasil Belajar pada Materi Nilai-Nilai Pancasila Siswa Kelas IV Sekolah Dasar - Lativa Ariani Sagita; Akhmad Junaedi (Paedagogie, 2026)
Teaching Pancasila in elementary schools requires teaching materials that can help students understand and apply the values of Pancasila in concrete ways in their daily lives. However, the use of interactive and contextual teaching materials remains limited, resulting in suboptimal student engagement and learning outcomes. This study aims to develop the KOJERUPAN (Pancasila Space Exploration Box) learning medium based on a smartbox that is valid, practical, and effective for improving student learning outcomes on Pancasila values. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 27 fourth-grade students at SDN Ngaliyan 03. Data collection techniques included observation, questionnaires, and learning outcome tests. The results showed that the KOJERUPAN medium received validation scores from subject matter experts and media experts with a percentage above 90% across all evaluation aspects, thus falling into the “highly valid” category. The practicality test results yielded a percentage of 99.65%, falling into the highly practical category. The effectiveness test results showed an increase in the average student score from 70.56 on the pretest to 82.96 on the posttest, with a t-test significance value of 0.00 < 0.05, and an N-Gain value of 0.43 in the moderate category. Based on these results, the smartbox-based KOJERUPAN medium was found to be highly valid, practical, and effective, making it suitable for use as an innovative alternative for teaching Pancasila in elementary schools.